f n ( x ) = x 2 + ( x + 1 ) 2 + ( x + 2 ) 2 + … + ( x + n ) 2
The function f n ( x ) is defined above for x ranges over all real values with natural number n .
If the minimum value of f n ( x ) is ( 2 1 0 − 1 2 ) then find the value of n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This approach is not correct. It has not proven that "the minimum occurs exactly at − 2 n . (Though yes, the statement is true)
What he did was:
1) Show that
f
(
x
)
≥
g
(
x
)
2) The minimum of
g
(
x
)
occurs at
x
∗
.
However, because equality doesn't occur in the Cauchy Schwarz that he set up, all that we have is f ( x ) > g ( x ) , and hence we are unable to conclude that the minimum of f occurs at x ∗ .
The approach would have worked if we had the additional condition
3)
f
(
x
∗
)
=
g
(
x
∗
)
.
In this case, we can conclude that
f
(
x
)
≥
g
(
x
)
≥
g
(
x
∗
)
=
f
(
x
∗
)
, and hence the minimum of
f
is at
x
∗
.
Umm sir, there are some minor typos in your solution .
I think it should be 2 1 0 in the 6th line from the bottom , and you have put one too many × in the 2nd last line .
Sorry, my mistake. I wasn't sure. I used calculus actually.
I solved it using the fact :
The minimum value of a x 2 + b x + c is c − b 2 / 4 a
Problem Loading...
Note Loading...
Set Loading...
f n ( x ) = x 2 + ( x + 1 ) 2 + ( x + 2 ) 2 + . . . + ( x + n ) 2
Differentiating and equating to zero, we have:
f ′ ( x ) f ′ ( x ) ⇒ 2 ( n + 1 ) x x = 2 x + 2 ( x + 1 ) + 2 ( x + 2 ) + . . . + 2 ( x + n ) = 2 ( n + 1 ) x + 2 n ( n + 1 ) = 0 = − 2 n ( n + 1 ) = − 2 n
We note that the lower limit of f n ( x ) ≥ 0 is when x = − 2 n . Therefore, minimum f n ( x ) is:
f n ( − 2 n ) = ( − 2 n ) 2 + ( 1 − 2 n ) 2 + ( 2 − 2 n ) 2 + . . . + ( 2 n ) 2 = ⎩ ⎨ ⎧ 2 [ 1 2 + 2 2 + 3 3 + . . . + ( 2 n ) 2 ] 2 [ ( 2 1 ) 2 + ( 2 3 ) 2 + ( 2 5 ) 2 + . . . + ( 2 n ) 2 ] for even n for odd n
Now 2 1 0 − 1 2 = 1 0 1 2 , assuming the required n is even, then:
2 [ 1 2 + 2 2 + 3 3 + . . . + ( 2 n ) 2 ] 6 2 2 n ( 2 n + 1 ) ( 2 2 n + 1 ) 1 2 n ( n + 2 ) ( n + 1 ) n ( n + 1 ) ( n + 2 ) ⇒ n = 1 0 1 2 = 1 0 1 2 = 1 0 1 2 = 2 2 × × 2 3 × 2 4 = 2 2